Tissue transglutaminase-induced alterations in extracellular matrix inhibit tumor invasion - Sahin Aysegul A; Arun Banu; Mangala Lingegowda S; Mehta Kapil (Molecular Cancer, 2005)
Abstract Background Alterations in the extracellular matrix (ECM) can affect host-tumor interactions and tumor growth and metastasis. Tissue transglutaminase (TG2, EC 2.3.2.13), a calcium-dependent enzyme that catalyzes covalent cross-linking of proteins, can render the ECM highly stable and resistant to proteolytic degradation. So we determined whether TG2 expression in a tumor or nontumor (stroma) environment could affect the process of metastasis. Two hundred archived samples from patients with breast cancer were studied for the TG2 expression. Also, in an in vitro model the invasive behavior of MDA-MB-231 cells in the presence or absence of exogenous TG2 was determined. Results Tumors associated with negative nodes showed significantly higher expression of TG2 in the stroma (P < 0.001). TG2 in the stroma was catalytically active, as revealed by the presence of isopeptide cross-links. Pretreatment of Matrigel with catalytically active TG2 resulted in strong inhibition of invasion of MDA-MB-231 cells through the Matrigel Transwell filters. Conclusion TG2-induced alterations in the ECM could effectively inhibit the process of metastasis. Therefore, selective induction of catalytically active TG2 at the site of tumor may offer promising approach for limiting the metastasis.